Kasandra - Schuller, Aleksandra (Keria (Ljubljana), 2001)
This article analyses the constitution and development of the woman's character in the ancient drama from the point of view of literary theory and anthropology. I interpret Priam's daughter and Trojan's prophet Cassandra as a paradigmatic example of an anthropological analysis of women's theme in the ancient as well as contemporary drama. In the essay I look closely at three dramas: the first part of Aeschylus Oresteia, the tragedy Agamemnon; at Euripides Trojan Women and at the drama Kasandra, written by the contemporary Slovenian author, Boris A. Novak. Incorporated into the research are also the literary images of Cassandra, as these were formed in the ancient epos (Lycophron's Alexandra) and contemporary novel (Christa Wolf's Kassandra).
Keywords: grška mitologija; Kasandra; literarna teorija; literarni motivi; žensko vprašanje